Bimtek Penyusunan Rencana Strategis BLUD UPTD Dinas Kesehatan Kabupaten Maros - Irwandy -; Noer Bahry Noor; Fridawaty Rivai; Adelia U. Ady Mangilep; Rini Anggraeni (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2022)
Based on the regulation of the Minister of Home Affairs number 79 of 2018 requires that all Regional Public Service Agencies (BLUD) including Puskesmas must develop a strategic plan as an administrative requirement for the establishment of BLUD. Several strategic changes have taken place since the creation of the Puskesmas strategic plan in Maros Regency including the Covid-19 pandemic until the publication of the Maros Regency Health Office Strategic Plan for the 2021-2026 period which must be a new reference for all UPTD health offices including puskesmas to develop a new strategic plan. Therefore, training was carried out targeting the improvement of knowledge and skills of health workers at the puskesmas in preparing strategic plans BLUD Puskesmas in accordance with the characteristics of the population, health problems faced, as well as policies and targets set by the Maros Regency government and the Health Office. The implementation was carried out within a period of 2 days in August 2022 with the Training of Trainer (ToT) method. Based on the results of the training evaluation, the presentation of the materials presented was able to be clearly understood by the trainees. This can be seen from the average level of knowledge of the participants (42 participants) before the training was only 39.7% and increased to 47.7% after the training related to the preparation of strategic plans BLUD Puskesmas, so it is expected to improve the quality of Service and performance BLUD Puskesmas.